Perpindahan Penduduk Fafanlap Ke Pulau Yellu Kecamatan Misool Selatan Kabupaten Raja Ampat Provinsi Papua Barat Daya - Loji, Siti Raguani; Touwe, Sem; Matitaputy, Jenny Koce (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2024)
This study aims to explore the population migration from Fafanlap to Yellu Island in South Misool District, Raja Ampat Regency, Southwest Papua Province. The research employs a qualitative method with data collection techniques, including observation, interviews, and documentation. This migration occurred around the 18th century during the reign of Sultan Nuku of Tidore. Driving factors for the migration included the less supportive environmental conditions in Fafanlap, such as the settlement pattern over water and crop damage by wild pigs. Additionally, the tax system imposed by the Tidore Sultanate added to the burden on the Fafanlap community. The main pull factor was the fertile and strategic natural conditions of Yellu Island, which was easier to monitor and manage. The research findings show that this migration significantly impacted various aspects of life in the Yellu community. In the social domain, there was an improvement in education and close interactions with neighbouring villages. Economically, the Yellu community experienced a diversification of livelihoods, including agriculture, fishing, and tourism. Yellu Island has become a tourist destination with homestays and other tourist facilities, helping to boost the local economy. Additionally, this migration strengthened the cultural identity of the Yellu community, preserving traditions and customs such as traditional rituals and communal work (mafabantuo). This study makes an essential contribution to understanding social dynamics and migration in the context of indigenous communities in Indonesia. The findings also offer valuable insights for further studies on population migration and resource management in remote areas.